Implementation of social responsibility activities in sport organisations (Laisvalaikio tyrimai, 2025)
Relevance and novelty of the article. Sport organisations are increasingly faced with growing expectations from the society, sponsors, and local communities to contribute to solving social and environmental problems. Fans particularly value corporate social responsibility (CSR) initiatives as an important part of forming their identity and loyalty (Tavares et al., 2023). In addition, CSR activities strengthen the financial stability of sport organisations and improve stakeholder satisfaction, which confirms their strategic value in the context of sustainable development (Chen, 2025). Finally, international standards and national sport strategies require greater transparency and accountability – CSR becomes not only a means of maintaining reputation, but also an essential part of the organisation’s operating philosophy. Although comprehensive CSR models are proposed in the global literature (e.g., Yang et al., 2024), in the regional context – especially in Lithuania and organisations in similar markets – there is a lack of empirical studies examining the real implementation of CSR initiatives in everyday practice. In addition, most studies are limited to declarations or retrospective reports, and grounded theory (grounded theory – measured theory), which refers to a qualitative research methodology, the essence of which is to derive (“measure”) the theory directly from the collected data, rather than applying an already existing theoretical model in advance. Models developed on the basis of which educational, health, communication, and ecological responsibility dimensions are distinguished (Zargar & Rynne, 2023) have not yet been practically tested in Lithuanian or Baltic sport organisations. Therefore, the orientation of this study towards the implementation and evaluation of social responsibility (SR) activities fills a clear scientific gap and provides practitioners with specific guidelines on how to effectively integrate CSR activities into their strategic management. Despite the increasing attention to this topic on a global scale, in Lithuania (or in the specific region) there is a lack of empirical research revealing the real practice of sport organisations, the content of activities, implementation challenges, and impact. This topic remains insufficiently researched at the local and national levels.Research problem. Does the implementation of SR activities have an impact on employees in a sport organisation?Research object. Implementation of SR activities.Research aim. To investigate how SR activities are implemented in sport organisations and what significance they have for the organisation’s activities and stakeholders.Objectives:• To reveal the concept of SR.• To discuss the content of SR activities in a sport organisation.Research methods:• Analysis of scientific literature.• Analysis of statistical data.• Questionnaire survey.The results. The concept of SR in a sport organisation has expanded from traditional charity-based activities to a complex strategic approach that includes both external and internal responsibility. Modern SR focuses not only on social projects or environmental protection, but also on employee well-being, emotional state, equal opportunities, work-life balance, and strengthening team culture. These measures are becoming an important part of the organisation’s strategy, especially in the sport sector, where employees experience greater emotional and physical stress. Analysis of research results shows that integrating SR activities into organisational management helps create a more sustainable, competitive, and ethical organisation, and the content of SR is constantly expanding in response to the expectations of employees and society. Employee well-being is a multifaceted phenomenon that encompasses physical, psychological, social, and professional well-being. A review of the research results has shown that areas such as emotional health, work-life balance, career opportunities, and a safe working environment are particularly important in the sport sector. Psychological capital, support from managers, and the involvement of organisational representatives in decision-making strengthen employee satisfaction, motivation, and loyalty to the organisation.Keywords: social responsibility, work environment, employees, sport organisation.